Evaluating concurrent enrollment composition courses for standards of composition, online teaching, and antiracist pedagogy - O'Bryan, Valarie Anderson (Kansas State University, 2022)
The demand for concurrent enrollment courses, which allow high school students to earn college credit and high school credit simultaneous, is increasing and more students than ever are using these courses as a bridge to their college education. Despite a history of marginalization, an increasing number of students of color are also joining concurrent enrollment courses. More than ever, instructors and institutions need to consider the needs of students of color in the design of concurrent enrollment coursework. Composition courses are commonly required general education requirements, meaning all students have to take them and pass them to continue with their college education. The first-year composition concurrent enrollment courses are among the highest in demand at high schools across the nation. If high school students taking concurrent enrollment composition courses fail, it will cost them more time and more money to continue their college career. For historically marginalized groups, especially students of color, failing concurrent enrollment composition courses could derail the rest of their academic career. Concurrent enrollment composition courses that incorporate antiracist pedagogy will benefit students of color by reducing barriers to their success. This dissertation evaluates an online concurrent enrollment course, first-year composition, for antiracist characteristics and makes suggestions for improvement. Antiracist pedagogy is the key to making the traditional college experience more equitable for all students, especially students of color.
Keywords: Online education; Antiracist pedagogy